2022
DOI: 10.1021/acs.inorgchem.2c03425
|View full text |Cite
|
Sign up to set email alerts
|

Hypercorroles Formed via the Tail that Wagged the Dog: Charge Transfer Interactions from Innocent Corroles to Meso-Nitrophenyl Substituents

Abstract: A series of cobalt nitrophenylcorroles were spectrally characterized in CH 2 Cl 2 , and under certain solution conditions, several compounds were shown to exhibit hypercorrole spectra resulting from charge transfer interactions from the corrole π-system to the redox-active meso-NO 2 Ph substituents. The resulting spectral pattern has not previously been reported for metallocorroles and in the case of the cobalt derivatives was shown to depend upon the number and position of the meso-nitrophenyl groups on the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 69 publications
0
19
0
Order By: Relevance
“…Our own laboratories have focused on elaborating an electrochemical litmus test for evaluating the innocence or noninnocence of transition-metal corroles ,,,,, and found that the presence of a facile reduction at potentials more positive than −0.20 V vs SCE (saturated calomel electrode) accompanied by a relatively small HOMO-LUMO gap (<1.0 V) could be used as an electrochemical diagnostic criterion to establish ligand noninnocence in these systems. Modulation of the orbital interactions, and thus the noninnocence of the corrole system, has been clearly demonstrated by changing the number and/or type of axial ligands bound to the central metal ion (mainly in the case of Mn, Fe, , and Co , derivatives), while the introduction of specific peripheral substituents has been suggested, in only a few cases, to facilitate conversion between the noninnocent [Cor •2– M II ] and innocent [Cor 3– M III ] configuration of the molecules.…”
Section: Introductionmentioning
confidence: 99%
“…Our own laboratories have focused on elaborating an electrochemical litmus test for evaluating the innocence or noninnocence of transition-metal corroles ,,,,, and found that the presence of a facile reduction at potentials more positive than −0.20 V vs SCE (saturated calomel electrode) accompanied by a relatively small HOMO-LUMO gap (<1.0 V) could be used as an electrochemical diagnostic criterion to establish ligand noninnocence in these systems. Modulation of the orbital interactions, and thus the noninnocence of the corrole system, has been clearly demonstrated by changing the number and/or type of axial ligands bound to the central metal ion (mainly in the case of Mn, Fe, , and Co , derivatives), while the introduction of specific peripheral substituents has been suggested, in only a few cases, to facilitate conversion between the noninnocent [Cor •2– M II ] and innocent [Cor 3– M III ] configuration of the molecules.…”
Section: Introductionmentioning
confidence: 99%
“…Silicon corroles have been utilized as excellent fluorescent F – sensors. , Lu and co-workers designed and synthesized a corrole probe exhibiting excellent sensitivity and selectivity for sulfide ions via chromogenic and fluorogenic signaling in living cells . Mono- and bis-cyano axially ligated cobalt triarylcorroles were synthesized and investigated spectroscopically and electrochemically in various solvents by Kadish and co-workers, and from this work, Nardis and co-workers developed an optical sensor based on (PPh 3 )­CoTTC/TDACl, which detects cyanide ions up to 0.053 mg/L …”
Section: Introductionmentioning
confidence: 99%
“…The reason is that, although all derivatives are present in the solid state (X-ray determination) as 6-coordinate complexes, they easily lose either one or even both axial ligands in dilute solutions. 21 The electron-richness of corroles is a major factor in that regard, coming into effect by 3 orders of magnitude differences in the bis(pyridine)cobalt(III) complex dissociation constants. 21,22 A plausible explanation is that the original pyridine ligands in the least Lewis acidic complex 3b are fully dissociated (presumably replaced by the coordinating acetonitrile solvent) even prior to reduction.…”
mentioning
confidence: 99%
“…21 The electron-richness of corroles is a major factor in that regard, coming into effect by 3 orders of magnitude differences in the bis(pyridine)cobalt(III) complex dissociation constants. 21,22 A plausible explanation is that the original pyridine ligands in the least Lewis acidic complex 3b are fully dissociated (presumably replaced by the coordinating acetonitrile solvent) even prior to reduction. Supporting evidence for this conclusion is based on two other observations: (a) the reoxidation process (i.e., the reverse scan) of [3b] − is maximal at −0.5 V, identical with the one assigned for PPh 3 -free [3t] − ; (b) while the second reduction of 2b occurs at a much less negative potential than that of 3b, consistent with the difference between them regarding the electron-withdrawing effect of CF 3 versus H, the opposite is true for their first reduction process.…”
mentioning
confidence: 99%
See 1 more Smart Citation